2021
DOI: 10.2106/jbjs.rvw.20.00116
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Balancing in Total Hip Arthroplasty

Abstract: » Appropriate total hip arthroplasty (THA) reconstruction must simultaneously address component position, restoration of biomechanics, and soft-tissue balance.» Preoperative planning for complex THA cases should include radiographic templating, a detailed case plan that contains backup implant options, and a thorough understanding of the patient’s preoperative examination.» Using a systematic approach to soft-tissue balancing in THA enhances the ability to intraoperatively execute the preoperative plan.» In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Martin et al concluded that the anatomy is better restored in a DAA when using fluoroscopy, compared to the posterior approach [ 23 ]. Moreover, Boe et al stated that using hip templating, restoring the anatomy and biomechanics can be achieved, and in combination with adequate soft-tissue balancing, a stable and ideal arthroplasty can be the result [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Martin et al concluded that the anatomy is better restored in a DAA when using fluoroscopy, compared to the posterior approach [ 23 ]. Moreover, Boe et al stated that using hip templating, restoring the anatomy and biomechanics can be achieved, and in combination with adequate soft-tissue balancing, a stable and ideal arthroplasty can be the result [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to conduct these releases systematically and titrate them as needed based on soft-tissue tightness; each release does have implications for soft-tissue balancing after hip reconstruction. 6 Again, it is imperative to understand that the soft tissues about the hip joint will stress relax during the procedure, which will result in continued enhanced acetabular exposure.…”
Section: Anterior Femoral Translation: Another 6 Stepsmentioning
confidence: 99%
“…On the other hand, in patients with the problem of compression of soft tissues with osteophytes which is difficult to diagnose abductor muscle weakness, muscle-tendon contractures related to surgical operations, bone deformations, length difference in the lower limbs, and bone protrusions and osteophytes that hinder the movement of the joint negatively affect the results of the surgery [6][7][8][9]. In these cases, great importance is attached to corrective procedures -excision of osteophytes that cause bone compression, restoration of abductor muscle strength, the balance of the joint center and provision of soft tissue balance in contracture muscles [10,11]. The ideas of Sir John Charnley, who first proposed and published the term "soft tissue balance", were later adopted by Dorr L.D.…”
Section: Introductionmentioning
confidence: 99%